Factors That Influence Refractive Changes in the First Year of Myopia Development in Premature Infants. (3rd June 2019) - Mao, Jianbo; Lao, Jimeng; Liu, Chenyi; Wu, Mingyuan; Yu, Xueting; Shao, Yirun; Zhu, Lin; Chen, Yiqi; Shen, Lijun
Abstract : Purpose . To study the development of refractive status from 36 weeks to one year of postmenstrual age and to identify factors that contribute to development of myopia, including gender, birth weight, gestational age, and retinopathy of prematurity (ROP). Methods . Premature infants underwent full cycloplegic retinoscopy at 36 weeks, 38 weeks, 40 weeks, 42 weeks, 44 weeks, 46 weeks, 48 weeks, 3 months, 6 months, 9 months, and 12 months of postmenstrual age. The infants were grouped by gender, birth weight, gestational age, and the severity of ROP to evaluate the correlation with refractive status at each postmenstrual age. Results . A total of 942 infants were recruited in this study. A total of 2716 readings were obtained. Refractive state had a hyperopic shift until 46 weeks of postmenstrual age ( r  = 0.42, P < 0.0001 ). After that, the mean spherical equivalent (SE) gradually declined ( r  = −0.30, P < 0.0001 ). Boys had lower hyperopia than girls at nine months ( t  = 3.10, P = 0.003 ) and one year ( t  = 3.34, P = 0.001 ) of postmenstrual age. Premature infants with ROP had a lower average SE at most of the postmenstrual ages; however, this value did not vary significantly (P > 0.05 ). Premature infants with severe ROP were less hyperopic than those without it at every postmenstrual age, and the average SE differed significantly at one year of postmenstrual age ( t  = 2.60, P = 0.011 ). There was no significant difference between each birth weight and gestational age (P > 0.05 ). Conclusions . The dioptric value of premature infants within one year was generally hyperopic. Different gender, birth weight, gestational age, and ROP did not affect the overall development of refractive status. Females may have higher hyperopia at nine months of postmenstrual age. Birth weight and gestational age had little effect on change of refractive status. Severe ROP was an important contributing factor in myopia progression, which may be related to the treatment required. Further study may be carried out to understand the mechanism behind myopia progression in premature infants, including changes in refractive system parameters and emmetropization process.